Digital Marketing Strategies for Sales Growth in Indonesian Home Industries - Rolando, Benediktus; Mulyono, Herry (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study investigates the role of digital marketing as a global marketing tool for enhancing sales in home industries within the digital economy era. Using a systematic literature review methodology through the PRISMA framework, the research analyzed 46 peer-reviewed articles to explore how home industry entrepreneurs implement digital marketing strategies to expand their market reach and improve sales performance. The findings indicate that the adoption of digital marketing significantly boosts visibility and sales for home industries, allowing them to connect with consumers beyond local markets. The study emphasizes that effective digital marketing methods foster a better understanding of consumer preferences, which is crucial for tailoring marketing efforts and enhancing customer engagement. Social media emerges as a critical component, facilitating direct interaction with consumers and providing real-time feedback essential for refining marketing strategies. The study's limitations include its focus on Indonesian home industries, potentially limiting generalizability, and its reliance on existing literature rather than primary data collection. The rapid evolution of digital technologies also suggests findings may require regular updates to remain relevant. The research has practical implications for home industry owners in implementing effective digital marketing strategies, for policymakers in supporting digital literacy and infrastructure development, and for practitioners in understanding the specific needs of home industries. The study also highlights that training and capacity-building initiatives are vital for empowering home industry owners to effectively utilize digital marketing tools, as many still lack adequate knowledge in this area. In conclusion, the integration of digital marketing strategies is essential for home industries to remain competitive in the global marketplace, driving sales growth and ensuring long-term sustainability in an increasingly digital world